Preparation method of antibacterial degradable sponge material

Through the multi-component collaborative design of protocatechic acid modified quaternized chitosan and quaternary ammonium salt grafted gelatin, the problem of balancing the existing antibacterial and degradable materials is solved, and the problem of balancing the antibacterial properties and degradability of existing antibacterial and degradable materials is achieved. Efficient, safe and environmentally friendly antibacterial and biodegradable material.

CN119391194AInactive Publication Date: 2025-02-07NANTONG FENGSHENG TEXTILE CO LTD

Patent Information

Application Number
CN202411990850.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing antibacterial and degradable materials have shortcomings in performance optimization, especially the balance between antibacterial and degradable properties is difficult to achieve, and there are also problems of toxic hazards and insufficient environmental protection.

Method used

The multi-component collaborative design of protocatechic acid modified quaternized chitosan and quaternary ammonium salt grafted gelatin is improved through precise assembly ratios and optimized preparation processes. Degradation performance.

Benefits of technology

It achieves diversification and long-term effectiveness of antibacterial properties, while improving the environmental adaptability and functional stability of the materials, overcomes the problem of attenuation of antibacterial effects of traditional materials in complex environments, and has higher purity and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391194A_ABST
    Figure CN119391194A_ABST
Patent Text Reader

Abstract

The invention relates to the field of sponge materials, and provides an antibacterial degradable sponge material and a preparation method thereof. The material is prepared from protocatechuic acid modified quaternized chitosan, quaternary ammonium salt grafted gelatin, sodium alginate, polyhydroxybutyrate, polycaprolactone, a polylactic acid-glycolic acid copolymer, hexamethylene diisocyanate, a foaming agent, nano cellulose, vitamin E, polyethylene glycol, triethylamine and dimethylformamide. Protocatechuic acid and quaternized chitosan are subjected to amidation modification, and chitosan and gelatin are subjected to quaternization treatment by adopting 2, 3-epoxypropyl trimethyl ammonium chloride, so that the antibacterial property and biodegradability of the material are improved. In the material preparation process, through vacuum degassing, foaming vacuum degree and humidity control and a multi-step drying process, it is ensured that the average pore size of the material is uniform (50-200 microns) and the porosity is high (50%-90%), and the obtained material has excellent antibacterial property and degradability and has wide application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sponge materials, and in particular to a method for preparing an antibacterial and degradable sponge material. Background Art

[0002] In the fields of environmental governance, food packaging, water treatment, etc., the demand for antibacterial and degradable materials is becoming increasingly prominent, and these application scenarios have put forward strict requirements on material performance. For example, in the field of food packaging, materials need to have good antibacterial properties to extend the shelf life of food and prevent bacterial contamination. At the same time, the materials are required to be able to degrade naturally after use to avoid the long-term pollution of the environment by traditional plastic packaging. In the field of water treatment, materials used for filtration or purification not only need to inhibit the growth of microorganisms and prevent bacteria from breeding in a humid environment, but also should be degraded into harmless substances within a certain period of time to avoid the formation of solid waste. In scenarios such as air purification, antibacterial and degradable materials can effectively capture and inhibit microbial particles in the air while reducing secondary pollution. The core needs in these fields are concentrated on the antibacterial property, degradability, environmental adaptability and safety of use of materials. Realizing efficient antibacterial and controllable degradation of materials can not only improve the performance and service life of products, but also effectively reduce the environmental burden and promote the application and development of green environmental protection technologies. Therefore, the development of a material with both excellent antibacterial properties and degradable characteristics is of great significance to meet practical application needs, broaden the functional range of products, and promote sustainable development.

[0003] Although antibacterial and biodegradable materials have achieved certain development in recent years, the existing technology still has many shortcomings in performance optimization. For example, a Chinese patent with publication number CN106700581A discloses a sponge material, the components of which include chlorinated polyethylene, zinc borate, magnesium hydroxide / aluminum hydroxide (flame retardant, etc.) and have poor degradability. Another Chinese patent with publication number CN109054102A discloses a degradable water-absorbing sponge, which has achieved good degradation performance, but has weak antibacterial properties and is easily ineffective in a humid or complex microbial environment. The main reason for these deficiencies is that it is difficult to achieve a balance in material properties: antibacterial properties usually rely on the addition of active antibacterial ingredients, which may weaken the degradability of the material; degradable materials often pursue the biodegradability of the molecular structure, but it is difficult to maintain long-term and stable antibacterial properties during use. In addition, some antibacterial agents in the prior art may have toxic risks or be easily released into the environment, further limiting the environmental protection and safety of the material. Therefore, how to effectively coordinate antibacterial properties and degradable properties in material design and develop efficient, safe and environmentally friendly multifunctional antibacterial degradable materials is a key issue to be urgently addressed in current research and application. Summary of the invention

[0004] (1) Technical issues solved The purpose of the present invention is to provide an antibacterial and degradable sponge material and a preparation method thereof, so as to solve the problem that the current sponge material has insufficient degradability and antibacterial properties.

[0005] (2) Technical solution In order to achieve the above object, the present invention provides the following technical solutions: An antibacterial and degradable sponge material comprises the following components in parts by weight: 8-12 parts of protocatechuic acid-modified quaternized chitosan, 10-20 parts of quaternary ammonium salt grafted gelatin, 5-10 parts of sodium alginate, 8-15 parts of polyhydroxybutyrate, 8-12 parts of polycaprolactone, 8-12 parts of polylactic acid-glycolic acid copolymer, 3-8 parts of gallic acid, 4-8 parts of foaming agent, 2-5 parts of nanocellulose, 0.5-2.0 parts of vitamin E, 8-16 parts of polyethylene glycol, 1.0-3.0 parts of triethylamine and 10-20 parts of dimethyl sulfoxide.

[0006] The protocatechuic acid modified quaternary ammonium chitosan is prepared from the following components in parts by weight: 6-12 parts of quaternary ammonium chitosan, 100 parts of 0.5wt.% acetic acid solution, 6-15 parts of protocatechuic acid, 50 parts of anhydrous ethanol, 150-200 parts of 2-(N-morpholine) ethanesulfonate potassium buffer with a pH of 5.5, 6-10 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, and 3.0-5.0 parts of N-hydroxysuccinimide.

[0007] The quaternized chitosan is obtained by modifying chitosan with 2,3-epoxypropyltrimethylammonium chloride.

[0008] The quaternary ammonium salt grafted gelatin is obtained by modifying gelatin with 2,3-epoxypropyltrimethylammonium chloride.

[0009] Further, the preparation method of the protocatechuic acid modified quaternized chitosan is as follows: by weight, 12 to 30 parts of quaternized chitosan are used as raw materials, and they are uniformly dissolved in 100 parts of 0.5wt% acetic acid solution to obtain solution A; 6 to 10 parts of protocatechuic acid are taken as raw materials and dissolved in 50 parts of anhydrous ethanol to obtain a mixed solution; 150 to 200 parts of 2-(N-morpholine) ethanesulfonic acid potassium buffer with a pH of 5.5 and 6 to 10 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added to the mixed solution, and stirred for 60 to 90 minutes to obtain solution B; 3.0 to 5.0 parts of N-hydroxysuccinimide are slowly added to solution B, and stirring is continued for 120 to 180 minutes to obtain solution C; solution C is added dropwise to solution A, and stirred at room temperature for 8 to 12 hours until the reaction is completed; after the reaction is completed, the mixed solution is heated to 3500 to 8000 in a molecular weight cutoff range. The Da dialysis membrane was dialyzed for 48-54 hours, and then the dialysate was centrifuged at 10000-12000 rpm for 20-30 minutes. After centrifugation, the supernatant was placed in a freeze dryer and freeze-dried for 4-8 hours at a vacuum degree of 4-10 Pa and a temperature of -30--10°C to finally obtain protocatechuic acid-modified quaternary ammonium chitosan.

[0010] Furthermore, the preparation method of the quaternized chitosan is as follows: in parts by weight, 14 to 20 parts of chitosan and 8.0 to 15.0 parts of 2,3-epoxypropyltrimethylammonium chloride are used as raw materials, and after being evenly mixed with 200 parts of deionized water, the mixture is placed in a three-necked flask, and stirred and refluxed at 75 to 85° C. for 20 to 28 hours until the reaction is completed; after the reaction is completed, the obtained solution is passed through a dialysis membrane with a molecular weight cutoff value of 1400, and dialyzed in distilled water for 60 to 72 hours; then the dialyzate is placed in a rotary evaporator, and concentrated to 1 / 5 to 1 / 10 of the original volume at 40 to 50° C. and a vacuum degree of -0.08 to -0.09 MPa. After the concentration is completed, the concentrated solution is placed in a freeze dryer, and freeze-dried for 6 to 12 hours at a vacuum degree of 4 to 10 Pa and a temperature of -30 to -10° C., to finally obtain a loose powdered quaternized chitosan.

[0011] Furthermore, the mass ratio of protocatechuic acid to quaternized chitosan is 1:(2.0-3.0).

[0012] The present invention adopts the design of protocatechuic acid modified quaternized chitosan mainly to enhance the antibacterial performance, environmental adaptability and functional stability of the material. By introducing the modification of protocatechuic acid on the basis of quaternized chitosan, the present invention realizes the synergistic optimization of antibacterial performance and structural stability. Quaternized chitosan, as a natural polysaccharide derivative with broad-spectrum antibacterial properties, significantly improves its antibacterial activity after quaternization modification, but its single antibacterial mechanism may lead to functional limitations in complex environments. Protocatechuic acid, as a naturally occurring polyphenol compound, has strong antioxidant and antibacterial capabilities. Through its covalent bonding with quaternized chitosan, it not only realizes the diversification of antibacterial mechanisms, but also effectively improves the environmental adaptability and long-term antibacterial performance of the modified material during use. In addition, the preparation process of the present invention fully reflects the synergy between the components. The activation process of protocatechuic acid is precisely controlled by a buffer system with a pH of 5.5 to ensure that it maintains high activity during the reaction; and the preparation of quaternized chitosan is quaternized by 2,3-epoxypropyltrimethylammonium chloride, which greatly improves the cationic density of chitosan, thereby enhancing its adsorption and destruction of bacterial cell membranes. The combination of the two is carried out slowly at room temperature by adding dropwise, avoiding the damage to the material properties under severe conditions, and removing the reaction residues through purification steps such as dialysis and freeze drying to ensure the high purity and high performance of the final product. In summary, the present invention realizes the diversification and long-term effect of antibacterial properties through the synergistic effect of protocatechuic acid and quaternized chitosan, while improving the environmental adaptability and functional stability of the material, providing new technical ideas and practical solutions for the development of antibacterial materials.

[0013] Furthermore, the preparation method of the quaternary ammonium salt grafted gelatin is as follows: by weight, 10 to 20 parts of gelatin are used as raw materials, dissolved in 150 to 200 parts of 10wt.% phosphate buffer, and stirred at 50 to 60°C for 30 to 60 minutes until completely dissolved; then the pH of the solution is adjusted to 8.5 to 9.0 with 1 mol / L sodium hydroxide solution, and the solution is kept in a stirring state; 40 to 50 parts of 50wt.% 2,3-epoxypropyltrimethylammonium chloride solution are slowly added dropwise to the solution, and the stirring reaction is continued at 50 to 60°C for 12 to 15 hours until the reaction is completed; the reaction solution is poured into a dialysis bag with a molecular weight cutoff value of 3000 to 3500 Da, and dialyzed in deionized water for 20 to 40 hours, and the deionized water is replaced every 5 hours; the dialyzed solution is placed in a -20 to 40°C environment and frozen for 10 to 14 hours, and finally the quaternary ammonium salt grafted gelatin is obtained.

[0014] Furthermore, the grafting rate of the quaternary ammonium salt grafted gelatin is 30% to 40%.

[0015] The present invention adopts the design of quaternary ammonium salt grafted gelatin mainly to enhance the antibacterial property and environmental stability of the material. By combining quaternary ammonium salt with gelatin molecular structure, the present invention realizes the synergistic optimization of antibacterial activity, structural stability and functional controllability. Gelatin, as a natural protein derivative, has good biocompatibility and film-forming property, but its antibacterial property is weak, and its structural stability is poor in a humid environment, and it is easy to hydrolyze or degrade. By introducing quaternary ammonium salt groups into gelatin molecules, not only the antibacterial property of the material is effectively improved, but also the durability of gelatin in a complex environment is enhanced. Quaternary ammonium salt has significant cationic properties, can be combined with bacterial cell membranes through electrostatic action, thereby destroying the cell membrane structure and inhibiting the growth of bacteria, and its chemical stability and hydrolysis resistance give the grafted material higher environmental adaptability. The technical scheme of the present invention ensures the synergy between the components by accurately controlling the preparation process of quaternary ammonium salt grafted gelatin. First, during the preparation process, gelatin is dissolved in phosphate buffer. By controlling the temperature and pH value of the solution, the activity and structural integrity of the gelatin molecules are maintained, providing a stable reaction basis for the subsequent grafting reaction. Subsequently, the 2,3-epoxypropyltrimethylammonium chloride solution is slowly introduced in a dropwise manner to ensure that the quaternary ammonium salt groups can be evenly distributed and fully react with the gelatin molecules, thereby improving the grafting efficiency and reducing the possibility of side reactions. The grafting reaction is carried out under mild conditions. By controlling the reaction time and temperature, excessive degradation of the gelatin molecules is avoided, thereby maintaining the mechanical properties and functional activity of the material. After the reaction is completed, unreacted impurities and small molecules are removed by dialysis, further improving the purity of the grafted gelatin. At the same time, the precise screening of molecular weight during dialysis is conducive to obtaining a uniform grafting rate, which is crucial to ensuring the antibacterial effect and environmental stability of the material. Finally, the finished product is obtained by freeze-drying technology, so that the grafted gelatin maintains a loose structural morphology, which is conducive to subsequent molding and processing.

[0016] The grafting rate of the quaternary ammonium salt grafted gelatin of the present invention is controlled between 30% and 40%, and this design fully balances the antibacterial performance and other functional characteristics of the material. A higher grafting rate can significantly enhance the antibacterial activity of the material, and an appropriate grafting degree avoids the problem of decreased biological performance or structural embrittlement of gelatin caused by an excessively high degree of quaternization, thereby ensuring the comprehensive performance of the material. Through the introduction of quaternary ammonium salts, the antibacterial performance, environmental stability and overall functionality of gelatin are significantly improved, fully reflecting the synergistic effect between the components, and providing a new technical path and theoretical basis for the development of antibacterial functional materials.

[0017] Furthermore, the foaming agent is sodium carbonate or sodium citrate.

[0018] Furthermore, the antibacterial and degradable sponge material has an average pore size of 50-200 μm and a porosity of 50%-90%.

[0019] Furthermore, the nanocellulose is Tempo-oxidized nanocellulose, and its surface carboxyl content is 1.0-2.0 mmol / g.

[0020] The present invention also provides a method for preparing an antibacterial and degradable sponge material, comprising the following steps: adding the mixture into a mixer according to a weight ratio, stirring at a rate of 300 to 500 rpm, stirring for 60 to 100 minutes, and controlling the system temperature at 40 to 50°C until a uniform mixed solution is formed; placing the obtained mixed solution in a vacuum environment, controlling the vacuum degree to be -0.08 to -0.1 MPa, and performing a degassing treatment for 10 to 20 minutes; pouring the degassed mixed solution into a mold, performing a foaming treatment in a vacuum environment, controlling the vacuum degree to be -0.06 to -0.08 MPa, and performing heat preservation and foaming at 40 to 50°C for 20 to 24 hours. h, until a uniform semi-cured material is formed; the semi-cured material formed after foaming is placed in an oven, and subjected to a primary drying treatment at 40-55°C, during which the humidity is controlled at 30%-50%, and the drying time is 3-6 h; finally, a final drying treatment is carried out at 50-55°C, the humidity is controlled at 5-8%, and the drying time is 6-10 h, to finally obtain an antibacterial and degradable sponge material.

[0021] The present invention adopts a multi-component collaborative design of protocatechuic acid-modified quaternized chitosan, quaternary ammonium salt grafted gelatin, sodium alginate, polyhydroxybutyrate, polycaprolactone and polylactic acid-glycolic acid copolymer, which is mainly used to enhance the antibacterial performance, environmental adaptability and degradability of antibacterial and degradable sponge materials. The present invention gives the material excellent performance and stable microstructure through scientific component matching and preparation process, thereby meeting the comprehensive requirements of antibacterial, degradable and mechanical properties. Biodegradable polymer combinations such as polyhydroxybutyrate, polycaprolactone and polylactic acid-glycolic acid copolymer constitute the main supporting structure of the material. These components can generate non-toxic small molecules by hydrolysis or biodegradation during the degradation process, thereby realizing the environmental protection and sustainability of the material. Among them, polyhydroxybutyrate gives the material higher rigidity and heat resistance, polycaprolactone provides good flexibility and ductility, and polylactic acid-glycolic acid copolymer optimizes the degradation rate by adjusting its molecular weight and copolymerization ratio, thereby realizing the synergistic effect of different components in the degradation process. As a filler, the abundant carboxyl groups on the surface of nanocellulose enhance the interfacial interaction of the material through hydrogen bonding or electrostatic interaction, while giving the material good mechanical properties and structural stability. The possible synergistic effect between protocatechuic acid-modified quaternized chitosan and quaternary ammonium salt-grafted gelatin can enhance the broad spectrum and durability of the antibacterial effect. As an antioxidant, vitamin E can effectively inhibit the oxidative degradation of the material during storage or use, thereby increasing the service life of the material.

[0022] The preparation process of the present invention ensures the uniform dispersion of components in the mixed solution and the stability of the pore structure of the material by precisely controlling key steps such as stirring, degassing and foaming. The use of a foaming agent (sodium carbonate or sodium citrate) generates gas in a vacuum environment to form a porous structure with a uniform average pore size, a pore size range of 50-200 μm, and a porosity of 50%-90%, which effectively improves the specific surface area and air permeability of the material, thereby enhancing its performance in the antibacterial and degradation processes. Through the step-by-step treatment of primary drying and final drying, the microstructure of the material is fully solidified and stabilized, while humidity control and temperature regulation avoid excessive shrinkage or deformation of the material. The introduction of polyethylene glycol and triethylamine further optimizes the processing performance and structural flexibility of the material. Dimethyl sulfoxide as a solvent not only promotes the uniform dispersion of components, but also ensures that the material does not produce undesirable byproducts during processing. Overall, the present invention achieves comprehensive optimization of the material's antibacterial properties, degradable properties and structural stability through the synergistic effect of multiple components combined with a scientific preparation process, providing an innovative technical solution for the development of antibacterial and degradable sponge materials.

[0023] (3) Beneficial technical effects 1. The present invention significantly improves the broad-spectrum antibacterial performance, environmental adaptability and long-term stability of antibacterial materials through the design of protocatechuic acid-modified quaternized chitosan. Compared with the prior art, the present invention realizes the diversification of antibacterial mechanisms and the persistence of functions, overcomes the problem of attenuation of antibacterial effects of traditional materials in complex environments, and has higher purity and safety, and has a wide range of application value. The present invention adopts precise component ratios and optimized preparation processes, and through the activation of protocatechuic acid and the efficient modification of quaternized chitosan, the chemical reactivity and compatibility of the two are improved, ensuring the efficient synergistic antibacterial effect of the material. Protocatechuic acid gives the material antioxidant function, and at the same time, through covalent bonding with quaternized chitosan, it realizes multiple destruction mechanisms of bacterial cell membranes, and dropwise addition, mitigation of reaction conditions and dialysis purification steps further ensure the performance stability and structural integrity of the material. The overall design is superior to the prior art in terms of antibacterial performance, environmental friendliness and safety, and provides strong technical support for the green, functional and long-term development of antibacterial materials.

[0024] 2. The present invention significantly improves the antibacterial performance and environmental stability of the material through the innovative design of quaternary ammonium salt grafted gelatin. Compared with the prior art, it has stronger antibacterial activity, more durable function, and excellent durability and structural stability in moist and complex environments. The biocompatibility and film-forming properties of gelatin combined with the cationic properties and hydrolysis resistance of quaternary ammonium salts not only achieve the diversification of antibacterial mechanisms, but also overcome the difficult problems of easy degradation and unstable antibacterial effects of traditional materials. The present invention balances antibacterial activity and mechanical properties by strictly controlling the grafting rate at 30% to 40%, while optimizing the preparation process, and ensuring the uniform distribution and synergistic effect of the components through mild reaction conditions and dialysis purification. The synergistic cooperation of the components in terms of antibacterial, stability and functionality provides innovative solutions and technical support for the development of functional antibacterial materials.

[0025] 3. The present invention significantly improves the antibacterial performance, environmental adaptability and degradability of antibacterial and degradable sponge materials through the collaborative design of multiple components such as protocatechuic acid-modified quaternized chitosan and quaternary ammonium salt grafted gelatin. Compared with the prior art, the present invention shows significant advantages in antibacterial activity, mechanical properties and sustainability. The combination of polyhydroxybutyrate, polycaprolactone and polylactic acid-glycolic acid copolymer provides synergistic optimization of rigidity, flexibility and controllable degradation rate, nanocellulose enhances interfacial interaction and mechanical properties, and the synergistic effect of protocatechuic acid-modified quaternized chitosan and quaternary ammonium salt grafted gelatin broadens the antibacterial spectrum and prolongs the antibacterial persistence. Through precise component ratio and preparation process, including foaming, degassing and multi-step drying treatment, the material forms a porous structure with uniform pore size and high porosity, improves air permeability and specific surface area, and solves the problem of insufficient antibacterial and stability of traditional materials in complex environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a microscopic morphology of the antibacterial and degradable sponge material prepared in Example 1 of the present invention.

[0027] Figure 2 This is the infrared Fourier spectrum of the chitosan of Example 1 of the present invention.

[0028] Figure 3 This is the infrared Fourier spectrum of the quaternized chitosan prepared in Example 1 of the present invention.

[0029] Figure 4 This is the infrared Fourier spectrum of the protocatechuic acid-modified quaternized chitosan prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0031] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.

[0032] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies Reagents company Sodium alginate Qingdao Yingfei Chemical Co., Ltd. Polyhydroxybutyrate Zhejiang Hangyu Pharmaceutical Technology Co., Ltd. Polycaprolactone Guangdong Wengjiang Chemical Reagent Co., Ltd. Poly(lactic-co-glycolic acid) Beijing Solable Technology Co., Ltd. gallic acid Shanghai MacLean Biochemical Technology Co., Ltd. Vitamin E Guangzhou Haoyu International Trade Co., Ltd. Polyethylene glycol Qianyan Chemical Technology (Wuhan) Co., Ltd. Triethylamine Shandong West Asia Chemical Co., Ltd. Dimethyl sulfoxide Shandong Mantanghong New Materials Co., Ltd. Acetic acid China National Pharmaceutical Group Corporation Anhydrous ethanol Shandong West Asia Chemical Co., Ltd. Protocatechuic acid Shanghai Kanglang Biotechnology Co., Ltd. Potassium 2-(N-morpholino)ethanesulfonate buffer Shandong West Asia Chemical Co., Ltd. 1-Ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride Hunan Yunbang Biotechnology Co., Ltd. N-Hydroxysuccinimide Shandong West Asia Chemical Co., Ltd. Chitosan Shandong West Asia Chemical Co., Ltd. 2,3-Epoxypropyltrimethylammonium chloride Suzhou Qihang Biotechnology Co., Ltd. gelatin Suzhou Qihang Biotechnology Co., Ltd. Phosphate buffered saline Shandong Mantanghong New Materials Co., Ltd. Sodium hydroxide Shanghai Ruiyan Petrochemical Co., Ltd. Tempo Oxidized Nanocellulose Nanjing Tianlu Nanotechnology Co., Ltd. Example 1

[0033] An antibacterial and degradable sponge material comprises the following components in parts by weight: 8 parts of protocatechuic acid-modified quaternized chitosan, 10 parts of quaternary ammonium salt grafted gelatin, 5 parts of sodium alginate, 8 parts of polyhydroxybutyrate, 8 parts of polycaprolactone, 8 parts of polylactic acid-glycolic acid copolymer, 3 parts of gallic acid, 4 parts of sodium carbonate, 2 parts of nanocellulose, 0.5 parts of vitamin E, 8 parts of polyethylene glycol, 1.0 part of triethylamine and 10 parts of dimethyl sulfoxide.

[0034] The protocatechuic acid-modified quaternized chitosan of this embodiment is prepared from the following components in parts by weight: 6 parts of quaternized chitosan, 100 parts of 0.5wt.% acetic acid solution, 6 parts of protocatechuic acid, 50 parts of anhydrous ethanol, 150 parts of 2-(N-morpholine) ethanesulfonate potassium buffer with a pH of 5.5, 6 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, and 3.0 parts of N-hydroxysuccinimide.

[0035] Quaternized chitosan is obtained by modifying chitosan with 2,3-epoxypropyltrimethylammonium chloride; quaternary ammonium salt grafted gelatin is obtained by modifying gelatin with 2,3-epoxypropyltrimethylammonium chloride.

[0036] The preparation method of the protocatechuic acid modified quaternized chitosan of the present embodiment is as follows: by weight, 12 parts of quaternized chitosan are used as raw materials, and they are uniformly dissolved in 100 parts of 0.5wt% acetic acid solution to obtain solution A; 6 parts of protocatechuic acid are taken as raw materials and dissolved in 50 parts of anhydrous ethanol to obtain a mixed solution; 150 parts of 2-(N-morpholine) ethanesulfonic acid potassium buffer with a pH of 5.5 and 6 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added to the mixed solution, and stirred for 60 minutes to obtain solution B; 3.0 parts of N-hydroxysuccinimide were slowly added to solution B, and stirring was continued for 120 minutes to obtain solution C; solution C was added dropwise to solution A, and stirred at room temperature for 8 hours until the reaction was completed; after the reaction was completed, the mixed solution was dialyzed on a dialysis membrane with a molecular weight cutoff range of 3500Da for 48 hours, and then the dialysate was centrifuged at 10000rpm for 20 minutes. After centrifugation, the supernatant was placed in a freeze dryer, and freeze-dried for 4 hours at a vacuum degree of 4Pa and a temperature of -30°C to finally obtain protocatechuic acid-modified quaternary ammonium chitosan.

[0037] The preparation method of the quaternized chitosan of the present embodiment is as follows: by weight, 14 parts of chitosan and 8.0 parts of 2,3-epoxypropyltrimethylammonium chloride are used as raw materials, and after being evenly mixed with 200 parts of deionized water, the mixture is placed in a three-necked flask, and stirred and refluxed at 75° C. for 20 hours until the reaction is completed; after the reaction is completed, the obtained solution is passed through a dialysis membrane with a molecular weight cutoff value of 1400Da, and dialyzed in distilled water for 60 hours; then the dialyzate is placed in a rotary evaporator, and concentrated to 1 / 5 of the original volume at 40° C. and a vacuum degree of -0.08MPa. After the concentration is completed, the concentrated solution is placed in a freeze dryer, and freeze-dried at a vacuum degree of 4Pa and a temperature of -30° C. for 6 hours to finally obtain loose powdered quaternized chitosan.

[0038] The preparation method of the quaternary ammonium salt grafted gelatin of the present embodiment is as follows: in parts by weight, 10 parts of gelatin are used as raw materials, dissolved in 150 parts of 10wt.% phosphate buffer, and stirred at 50°C for 30 minutes until completely dissolved; then the pH of the solution is adjusted to 8.5 with 1 mol / L sodium hydroxide solution, and the solution is kept in a stirring state; 40 parts of 50wt.% 2,3-epoxypropyltrimethylammonium chloride solution are slowly added dropwise to the solution, and the stirring reaction is continued at 50°C for 12 hours until the reaction is completed; the reaction solution is poured into a dialysis bag with a molecular weight cutoff value of 3000Da, and dialyzed in deionized water for 20 hours, with the deionized water replaced every 5 hours; the dialyzed solution is placed in a -20°C environment and frozen for 10 hours to finally obtain the quaternary ammonium salt grafted gelatin.

[0039] The grafting rate of the quaternary ammonium salt grafted gelatin in this embodiment is 30%. The foaming agent is sodium carbonate; the average pore size of the antibacterial and degradable sponge material is 50 μm, and the porosity is 50%; the nanocellulose is Tempo oxidized nanocellulose, and the surface carboxyl content is 1.0 mmol / g.

[0040] The present embodiment provides a method for preparing an antibacterial and degradable sponge material, comprising the following steps: adding into a mixer according to a weight ratio, with a stirring rate of 300 rpm, a stirring time of 60 min, and a system temperature controlled at 40°C, until a uniform mixed liquid is formed; placing the obtained mixed liquid in a vacuum environment, controlling the vacuum degree to -0.08 MPa, and degassing for 10 min; pouring the degassed mixed liquid into a mold, foaming it in a vacuum environment, controlling the vacuum degree to -0.06 MPa, and keeping it warm for foaming at 40°C for 20 hours, until a uniform semi-cured material is formed; placing the semi-cured material formed after foaming in an oven, performing an initial drying treatment at 40°C, controlling the humidity at 30% during the initial drying process, and drying for 3 hours, and finally performing a final drying treatment at 50°C, controlling the humidity at 5%, and drying for 6 hours, to finally obtain an antibacterial and degradable sponge material.

[0041] Figure 1 The microscopic morphology of the antibacterial and degradable sponge material prepared in Example 1 of the present invention can clearly show the porous sponge morphology. Through the analysis of the infrared Fourier transform spectrum, it can be concluded that the structures of the quaternized chitosan and the protocatechuic acid-modified quaternized chitosan prepared in Example 1 of the present invention have been clearly verified. Figure 2 The infrared Fourier spectrum of chitosan prepared in Example 1 is shown. Figure 3 is the infrared Fourier spectrum of quaternized chitosan. Figure 4 This is the infrared Fourier spectrum of quaternized chitosan modified with protocatechuic acid. In the infrared spectrum of quaternized chitosan, the characteristic peak at 1480 cm⁻¹ indicates that the trimethylammonium group is successfully introduced into the chitosan skeleton, and the NH bending peak (1587 cm⁻¹) of the primary amine is weakened, indicating that the primary amine is partially converted into a secondary amine. In addition, the OH stretching vibration peak in the range of 3500-3200 cm⁻¹ and the NH stretching vibration peak at 2920 cm⁻¹ further support the formation of the quaternary ammonium salt structure. Figure 4In the infrared spectrum of protocatechuic acid-modified quaternized chitosan, the characteristic peaks of amide bonds at 1624 cm⁻¹, 1587 cm⁻¹ and 1354 cm⁻¹ correspond to the C=O stretching of amide bond I, the NH bending of amide bond II and the CN stretching of amide bond III, respectively, indicating that protocatechuic acid is successfully coupled to quaternized chitosan through amide bonds. In addition, the significant decrease in the primary NH bending absorption peak at 2920 cm⁻¹ further proves that protocatechuic acid undergoes an amidation reaction with the amino group of quaternized chitosan, verifying the structural changes of the modified chitosan. The changes in these characteristic peaks clearly indicate that the quaternization of chitosan and the subsequent protocatechuic acid modification in the present invention have been successfully achieved. Example 2

[0042] An antibacterial and degradable sponge material comprises the following components in parts by weight: 9 parts of protocatechuic acid-modified quaternized chitosan, 13 parts of quaternary ammonium salt grafted gelatin, 7 parts of sodium alginate, 10 parts of polyhydroxybutyrate, 9 parts of polycaprolactone, 9 parts of polylactic acid-glycolic acid copolymer, 5 parts of gallic acid, 5 parts of sodium citrate, 3 parts of nanocellulose, 1.0 part of vitamin E, 10 parts of polyethylene glycol, 1.6 parts of triethylamine and 13 parts of dimethyl sulfoxide.

[0043] The protocatechuic acid-modified quaternized chitosan of this embodiment is prepared from the following components in parts by weight: 8 parts of quaternized chitosan, 100 parts of 0.5wt.% acetic acid solution, 9 parts of protocatechuic acid, 50 parts of anhydrous ethanol, 165 parts of 2-(N-morpholine) ethanesulfonate potassium buffer with a pH of 5.5, 7 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, and 3.6 parts of N-hydroxysuccinimide.

[0044] Quaternized chitosan is obtained by modifying chitosan with 2,3-epoxypropyltrimethylammonium chloride; quaternary ammonium salt grafted gelatin is obtained by modifying gelatin with 2,3-epoxypropyltrimethylammonium chloride.

[0045] The preparation method of the protocatechuic acid modified quaternized chitosan of the present embodiment is as follows: by weight, 17 parts of quaternized chitosan are used as raw materials, and they are uniformly dissolved in 100 parts of 0.5wt% acetic acid solution to obtain solution A; 7 parts of protocatechuic acid are taken as raw materials and dissolved in 50 parts of anhydrous ethanol to obtain a mixed solution; 165 parts of 2-(N-morpholine) ethanesulfonic acid potassium buffer with a pH of 5.5 and 7 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added to the mixed solution, and stirred for 69 minutes to obtain solution B; 3.6 parts of N-hydroxysuccinimide were slowly added to solution B, and stirring was continued for 138 minutes to obtain solution C; solution C was added dropwise to solution A, and stirred at room temperature for 9 hours until the reaction was completed; after the reaction was completed, the mixed solution was dialyzed for 50 hours on a dialysis membrane with a molecular weight cutoff range of 4850Da, and then the dialyzate was centrifuged at 10600rpm for 23 minutes. After centrifugation, the supernatant was placed in a freeze dryer, and freeze-dried for 5 hours at a vacuum degree of 6Pa and a temperature of -24°C to finally obtain protocatechuic acid-modified quaternary ammonium chitosan.

[0046] The preparation method of the quaternized chitosan of the present embodiment is as follows: by weight, 16 parts of chitosan and 10.1 parts of 2,3-epoxypropyltrimethylammonium chloride are used as raw materials, and after being evenly mixed with 200 parts of deionized water, the mixture is placed in a three-necked flask, and stirred and refluxed at 78° C. for 22 hours until the reaction is completed; after the reaction is completed, the obtained solution is passed through a dialysis membrane with a molecular weight cutoff value of 1400, and dialyzed in distilled water for 64 hours; then the dialyzate is placed in a rotary evaporator, and concentrated to 1 / 6 of the original volume at 43° C. and a vacuum degree of -0.083 MPa. After the concentration is completed, the concentrated solution is placed in a freeze dryer, and freeze-dried at a vacuum degree of 6 Pa and a temperature of -24° C. for 8 hours to finally obtain loose powdered quaternized chitosan.

[0047] The preparation method of the quaternary ammonium salt grafted gelatin of the present embodiment is as follows: by weight, 13 parts of gelatin are used as raw materials, dissolved in 165 parts of 10wt.% phosphate buffer, and stirred at 53°C for 39 minutes until completely dissolved; then the pH of the solution is adjusted to 8.7 with 1 mol / L sodium hydroxide solution, and the solution is kept in a stirring state; 43 parts of 50wt.% 2,3-epoxypropyltrimethylammonium chloride solution are slowly added dropwise to the solution, and the stirring reaction is continued at 53°C for 13 hours until the reaction is completed; the reaction solution is poured into a dialysis bag with a molecular weight cutoff value of 3150Da, and dialyzed in deionized water for 26 hours, with the deionized water replaced every 5 hours; the dialyzed solution is placed in a -8°C environment and frozen for 11 hours to finally obtain the quaternary ammonium salt grafted gelatin.

[0048] The grafting rate of the quaternary ammonium salt grafted gelatin in this embodiment is 33%; the average pore size of the antibacterial and degradable sponge material is 95 μm, and the porosity is 62%; the nanocellulose is Tempo oxidized nanocellulose, and its surface carboxyl content is 1.3 mmol / g.

[0049] The present embodiment provides a method for preparing an antibacterial and degradable sponge material, comprising the following steps: adding into a mixer according to a weight ratio, with a stirring rate of 360 rpm, a stirring time of 72 min, and a system temperature controlled at 43°C, until a uniform mixed solution is formed; placing the obtained mixed solution in a vacuum environment, controlling the vacuum degree to -0.086 MPa, and performing a degassing treatment for 13 min; pouring the degassed mixed solution into a mold, performing a foaming treatment in a vacuum environment, controlling the vacuum degree to -0.066 MPa, and keeping the mixture warm at 43°C for 21 h, until a uniform semi-cured material is formed; placing the semi-cured material formed after foaming in an oven, performing an initial drying treatment at 45°C, controlling the humidity at 36% during the initial drying process, and performing a drying time of 4 h, and finally performing a final drying treatment at 52°C, controlling the humidity at 6%, and performing a drying time of 7 h, to finally obtain an antibacterial and degradable sponge material. Example 3

[0050] An antibacterial and degradable sponge material comprises the following components in parts by weight: 10 parts of protocatechuic acid-modified quaternized chitosan, 16 parts of quaternary ammonium salt grafted gelatin, 8 parts of sodium alginate, 12 parts of polyhydroxybutyrate, 10 parts of polycaprolactone, 10 parts of polylactic acid-glycolic acid copolymer, 6 parts of gallic acid, 6 parts of sodium carbonate, 4 parts of nanocellulose, 1.4 parts of vitamin E, 13 parts of polyethylene glycol, 2.2 parts of triethylamine and 16 parts of dimethyl sulfoxide.

[0051] The protocatechuic acid-modified quaternized chitosan of this embodiment is prepared from the following components in parts by weight: 10 parts of quaternized chitosan, 100 parts of 0.5wt.% acetic acid solution, 11 parts of protocatechuic acid, 50 parts of anhydrous ethanol, 180 parts of 2-(N-morpholine)ethanesulfonate potassium buffer with a pH of 5.5, 8 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 4.2 parts of N-hydroxysuccinimide.

[0052] Quaternized chitosan is obtained by modifying chitosan with 2,3-epoxypropyltrimethylammonium chloride; quaternary ammonium salt grafted gelatin is obtained by modifying gelatin with 2,3-epoxypropyltrimethylammonium chloride.

[0053] The preparation method of the protocatechuic acid modified quaternized chitosan of the present embodiment is as follows: by weight, 23 parts of quaternized chitosan are used as raw materials, and they are uniformly dissolved in 100 parts of 0.5wt% acetic acid solution to obtain solution A; 8 parts of protocatechuic acid are taken as raw materials and dissolved in 50 parts of anhydrous ethanol to obtain a mixed solution; 180 parts of 2-(N-morpholine) ethanesulfonic acid potassium buffer with a pH of 5.5 and 8 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added to the mixed solution, and stirred for 78 minutes to obtain solution B; 4.2 parts of N-hydroxysuccinimide were slowly added to solution B, and stirring was continued for 156 minutes to obtain solution C; solution C was added dropwise to solution A, and stirred at room temperature for 10 hours until the reaction was completed; after the reaction was completed, the mixed solution was dialyzed for 52 hours on a dialysis membrane with a molecular weight cutoff range of 6200Da, and then the dialyzate was centrifuged at 11200rpm for 26 minutes. After centrifugation, the supernatant was placed in a freeze dryer, and freeze-dried for 6 hours at a vacuum degree of 8Pa and a temperature of -18°C to finally obtain protocatechuic acid-modified quaternary ammonium chitosan.

[0054] The preparation method of the quaternized chitosan of the present embodiment is as follows: by weight, 18 parts of chitosan and 12.2 parts of 2,3-epoxypropyltrimethylammonium chloride are used as raw materials, and the mixture is uniformly mixed with 200 parts of deionized water, and then placed in a three-necked flask, and stirred and refluxed at 81° C. for 25 hours until the reaction is completed; after the reaction is completed, the obtained solution is passed through a dialysis membrane with a molecular weight cutoff value of 1400, and dialyzed in distilled water for 67 hours; then the dialyzate is placed in a rotary evaporator, and concentrated to 1 / 8 of the original volume at 46° C. and a vacuum degree of -0.086 MPa. After the concentration is completed, the concentrated solution is placed in a freeze dryer, and freeze-dried for 10 hours at a vacuum degree of 8 Pa and a temperature of -18° C., and finally a loose powdery quaternized chitosan is obtained.

[0055] The preparation method of the quaternary ammonium salt grafted gelatin of the present embodiment is as follows: by weight, 16 parts of gelatin are used as raw materials, dissolved in 180 parts of 10wt.% phosphate buffer, and stirred at 56°C for 48 minutes until completely dissolved; then the pH of the solution is adjusted to 8.8 with 1 mol / L sodium hydroxide solution, and the solution is kept in a stirring state; 46 parts of 50wt.% 2,3-epoxypropyltrimethylammonium chloride solution are slowly added dropwise to the solution, and the stirring reaction is continued at 56°C for 14 hours until the reaction is completed; the reaction solution is poured into a dialysis bag with a molecular weight cutoff value of 3300Da, and dialyzed in deionized water for 32 hours, with the deionized water replaced every 5 hours; the dialyzed solution is placed in a 4°C environment and frozen for 12 hours to finally obtain the quaternary ammonium salt grafted gelatin.

[0056] The grafting rate of the quaternary ammonium salt grafted gelatin in this embodiment is 36%. The average pore size of the antibacterial and degradable sponge material is 140 μm, and the porosity is 74%; the nanocellulose is Tempo oxidized nanocellulose, and the surface carboxyl content is 1.6 mmol / g.

[0057] The present embodiment provides a method for preparing an antibacterial and degradable sponge material, comprising the following steps: adding into a mixer according to a weight ratio, with a stirring rate of 420 rpm, a stirring time of 84 min, and a system temperature controlled at 46°C, until a uniform mixed solution is formed; placing the obtained mixed solution in a vacuum environment, controlling the vacuum degree to -0.092 MPa, and performing a degassing treatment for 16 min; pouring the degassed mixed solution into a mold, performing a foaming treatment in a vacuum environment, controlling the vacuum degree to -0.072 MPa, and keeping the mixture warm at 46°C for 22 h, until a uniform semi-cured material is formed; placing the semi-cured material formed after foaming in an oven, performing an initial drying treatment at 49°C, controlling the humidity at 42% during the initial drying process, and performing a drying time of 5 h, and finally performing a final drying treatment at 53°C, controlling the humidity at 7%, and performing a drying time of 8 h, to finally obtain an antibacterial and degradable sponge material. Example 4

[0058] An antibacterial and degradable sponge material comprises the following components in parts by weight: 12 parts of protocatechuic acid-modified quaternized chitosan, 20 parts of quaternary ammonium salt grafted gelatin, 10 parts of sodium alginate, 15 parts of polyhydroxybutyrate, 12 parts of polycaprolactone, 12 parts of polylactic acid-glycolic acid copolymer, 8 parts of gallic acid, 8 parts of sodium citrate, 5 parts of nanocellulose, 2.0 parts of vitamin E, 16 parts of polyethylene glycol, 3.0 parts of triethylamine and 20 parts of dimethyl sulfoxide.

[0059] The protocatechuic acid-modified quaternized chitosan of this embodiment is prepared from the following components in parts by weight: 12 parts of quaternized chitosan, 100 parts of 0.5wt.% acetic acid solution, 15 parts of protocatechuic acid, 50 parts of anhydrous ethanol, 200 parts of 2-(N-morpholine) ethanesulfonate potassium buffer with a pH of 5.5, 10 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, and 5.0 parts of N-hydroxysuccinimide.

[0060] Quaternized chitosan is obtained by modifying chitosan with 2,3-epoxypropyltrimethylammonium chloride; quaternary ammonium salt grafted gelatin is obtained by modifying gelatin with 2,3-epoxypropyltrimethylammonium chloride.

[0061] The preparation method of the protocatechuic acid modified quaternized chitosan of the present embodiment is as follows: by weight, 30 parts of quaternized chitosan are used as raw materials, and they are uniformly dissolved in 100 parts of 0.5wt% acetic acid solution to obtain solution A; 10 parts of protocatechuic acid are taken as raw materials and dissolved in 50 parts of anhydrous ethanol to obtain a mixed solution; 200 parts of 2-(N-morpholine) ethanesulfonic acid potassium buffer with a pH of 5.5 and 10 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added to the mixed solution, and stirred for 90 minutes to obtain solution B; 5.0 parts of N-hydroxysuccinimide were slowly added to solution B, and stirring was continued for 180 minutes to obtain solution C; solution C was added dropwise to solution A, and stirred at room temperature for 12 hours until the reaction was completed; after the reaction was completed, the mixed solution was dialyzed on a dialysis membrane with a molecular weight cutoff range of 8000Da for 54 hours, and then the dialyzate was centrifuged at 12000rpm for 30 minutes. After centrifugation, the supernatant was placed in a freeze dryer, and freeze-dried for 8 hours at a vacuum degree of 10Pa and a temperature of -10°C to finally obtain protocatechuic acid-modified quaternary ammonium chitosan.

[0062] The preparation method of the quaternized chitosan of the present embodiment is as follows: by weight, 20 parts of chitosan and 15.0 parts of 2,3-epoxypropyltrimethylammonium chloride are used as raw materials, and the mixture is uniformly mixed with 200 parts of deionized water, and then placed in a three-necked flask, and stirred and refluxed at 85° C. for 28 hours until the reaction is completed; after the reaction is completed, the obtained solution is passed through a dialysis membrane with a molecular weight cutoff value of 1400, and dialyzed in distilled water for 72 hours; then the dialyzate is placed in a rotary evaporator, and concentrated to 1 / 10 of the original volume at 50° C. and a vacuum degree of -0.09 MPa. After the concentration is completed, the concentrated solution is placed in a freeze dryer, and freeze-dried for 12 hours at a vacuum degree of 10 Pa and a temperature of -10° C., and finally a loose powdery quaternized chitosan is obtained.

[0063] The preparation method of the quaternary ammonium salt grafted gelatin of the present embodiment is as follows: in parts by weight, 20 parts of gelatin are used as raw materials, dissolved in 200 parts of 10wt.% phosphate buffer, and stirred at 60°C for 60 minutes until completely dissolved; then the pH of the solution is adjusted to 9.0 with 1 mol / L sodium hydroxide solution, and the solution is kept in a stirring state; 50 parts of 50wt.% 2,3-epoxypropyltrimethylammonium chloride solution are slowly added dropwise to the solution, and the stirring reaction is continued at 60°C for 15 hours until the reaction is completed; the reaction solution is poured into a dialysis bag with a molecular weight cutoff value of 3500Da, and dialyzed in deionized water for 40 hours, with the deionized water replaced every 5 hours; the dialyzed solution is placed in a 40°C environment and frozen for 14 hours to finally obtain the quaternary ammonium salt grafted gelatin.

[0064] The grafting rate of the quaternary ammonium salt grafted gelatin in this embodiment is 40%. The average pore size of the antibacterial and degradable sponge material is 200 μm, and the porosity is 90%; the nanocellulose is Tempo oxidized nanocellulose, and the surface carboxyl content is 2.0 mmol / g.

[0065] The present embodiment provides a method for preparing an antibacterial and degradable sponge material, comprising the following steps: adding into a mixer according to a weight ratio, with a stirring rate of 500 rpm, a stirring time of 100 min, and a system temperature controlled at 50°C, until a uniform mixed solution is formed; placing the obtained mixed solution in a vacuum environment, controlling the vacuum degree to -0.1 MPa, and performing a degassing treatment for 20 min; pouring the degassed mixed solution into a mold, performing a foaming treatment in a vacuum environment, controlling the vacuum degree to -0.08 MPa, and keeping the mixture warm at 50°C for 24 hours, until a uniform semi-cured material is formed; placing the semi-cured material formed after foaming in an oven, performing an initial drying treatment at 55°C, controlling the humidity at 50% during the initial drying process, and performing a drying time of 6 hours, and finally performing a final drying treatment at 55°C, controlling the humidity at 8%, and performing a drying time of 10 hours, to finally obtain an antibacterial and degradable sponge material.

[0066] Comparative Example 1 The method is basically the same as Example 1, except that the quaternized chitosan is not modified with protocatechuic acid.

[0067] Comparative Example 2 The method is basically the same as Example 1, except that the chitosan is not quaternized by 2,3-epoxypropyltrimethylammonium chloride.

[0068] Comparative Example 3 The method is basically the same as Example 1, except that in the preparation of protocatechuic acid-modified quaternized chitosan, the amount of ammonium chitosan is 12 parts, and the amount of protocatechuic acid is 12 parts, so the mass ratio of protocatechuic acid to quaternized chitosan is 1:1.

[0069] Comparative Example 4 The method is basically the same as Example 1, except that in the preparation of protocatechuic acid-modified quaternized chitosan, the ammonium chitosan is 24 parts and the protocatechuic acid is 6 parts, so the mass ratio of protocatechuic acid to quaternized chitosan is 1:4.

[0070] Comparative Example 5 The method is basically the same as Example 1, except that the gelatin is not grafted with 2,3-epoxypropyltrimethylammonium chloride.

[0071] Comparative Example 6 It is basically the same as Example 1, except that 30 parts of 50wt.% 2,3-epoxypropyltrimethylammonium chloride solution are used to prepare the quaternary ammonium salt grafted gelatin, and the grafting rate of the quaternary ammonium salt grafted gelatin is 25%.

[0072] Comparative Example 7 It is basically the same as Example 1, except that 55 parts of 50wt.% 2,3-epoxypropyltrimethylammonium chloride solution are used to prepare the quaternary ammonium salt grafted gelatin, and the grafting rate of the quaternary ammonium salt grafted gelatin is 45%.

[0073] Performance Test: Antibacterial test: The effect of sponge samples on the survival of Escherichia coli and Staphylococcus aureus was used as the test index. First, the sponge samples were sterilized under ultraviolet light for 120 minutes. 25 mg of sponge samples were taken and placed in 800 μL of sterile PBS solution (pH=7.4) and 20 μL of 10 6 CFU / mL of bacterial suspension, incubated at 37°C shaker for 4 hours. After incubation, 50μL of bacterial suspension was spread on the plate and incubated in a 37°C incubator for 24 hours, and then the number of colonies on the plate was counted. The blank control group was a bacterial suspension without sponge. The antibacterial rate (Antibacterialratio) was calculated according to the following formula: Antibacterialratio(%)=((C1-C2) / C1)×100%, where C1 is the number of colonies in the control group and C2 is the number of colonies in the sponge experimental group. The antibacterial rate was calculated based on the test results of three parallel samples and expressed as the arithmetic mean and standard deviation (M±SD, n=3).

[0074] Mechanical properties: The sponge samples were immersed in phosphate buffer saline (PBS, pH 7.4) to achieve swelling equilibrium, and then the size was measured and recorded using a vernier caliper. Then, the swollen sponge samples were subjected to compression performance tests using an electronic universal material testing machine, with the compression rate set to 5 mm / min. To ensure the normal operation of the universal testing machine, the maximum compression strain was set to 95% of the maximum strain to obtain the maximum compression stress (i.e., compression strength). In addition, the toughness of the sponge sample was calculated by integrating the area under the stress-strain curve, and the compression modulus was calculated by the ratio of stress to strain. The test of each sponge sample was repeated 5 times, and the final results were expressed as the arithmetic mean and standard deviation (M±SD, n=5) of toughness and compression modulus.

[0075] Degradability: The initial weight of the sponge sample was weighed and recorded as W1, and it was completely immersed in a phosphate buffered saline solution (pH = 7.4) containing lysozyme (0.5 mg / mL) to test the in vitro degradation behavior of the sponge sample. During the experiment, a new phosphate buffered saline solution containing lysozyme was replaced every three days. At the same time, the sponge sample was taken out on the 14th day, and after vacuum drying, it was weighed again and recorded as W2. The in vitro degradation rate (Degradation rate) was calculated according to the formula Degradation rate (%) = ((W1 - W2) / W1) × 100%, where W1 and W2 are the initial weight and final weight of the sponge sample after drying, respectively. The test results of the degradation rate are calculated based on three parallel samples and are finally expressed as the arithmetic mean and standard deviation (M±SD, n=3).

[0076] The properties of the sponge materials of Examples 1 to 4 and Comparative Examples 1 to 7 are summarized in Table 2.

[0077] Table 2 Performance of sponge materials of Examples 1 to 4 and Comparative Examples 1 to 7

[0078] The main difference between Comparative Example 1 and Example 1 is that quaternized chitosan in Comparative Example 1 is not modified by protocatechuic acid. As can be seen from the table, the quaternized chitosan without protocatechuic acid modification causes a significant reduction in antibacterial property, while compressive strength, toughness and degradation rate also have a significant decrease. The reason for the reduction in antibacterial property is that protocatechuic acid modification can introduce phenolic hydroxyl groups, which enhances the antibacterial activity of quaternized chitosan, while the antibacterial properties of unmodified quaternized chitosan are weaker. The reason for the reduction in compressive strength and toughness is that the introduction of protocatechuic acid can improve the intermolecular bonding force of the material by forming hydrogen bonds and crosslinking, and enhance mechanical properties, while the unmodified material lacks this enhancement effect. The reason for the decrease in degradation rate is that the introduction of protocatechuic acid can improve the degradability of the material, while the unmodified material degradation efficiency is low.

[0079] The main difference between Comparative Example 2 and Example 1 is that chitosan in Comparative Example 2 is not quaternized with 2,3-epoxypropyltrimethylammonium chloride. As can be seen from the table, chitosan that has not been quaternized leads to significant reductions in antibacterial properties, compressive strength, toughness and degradation rate. The reason for the reduction in antibacterial properties is that the quaternization treatment can introduce positive charges, enhance the adsorption and bactericidal ability of chitosan on bacterial cell membranes, and the antibacterial effect of unquaternized chitosan is poor. The reason for the decrease in mechanical properties and toughness is that the quaternization treatment improves the compatibility and intermolecular binding force of chitosan with other components, while the molecular structure of untreated chitosan is loose, resulting in poor compressive strength and toughness. The reason for the decrease in degradation rate is that the quaternization treatment of chitosan can improve the water solubility and biodegradability of the material under degradation conditions, while the degradation efficiency of unmodified chitosan is low.

[0080] The main difference between Comparative Example 3 and Example 1 is that the mass ratio of protocatechuic acid to quaternized chitosan in Comparative Example 3 is 1:1, while that in Example 1 is 1:2. As can be seen from the table, a high protocatechuic acid ratio (1:1) will lead to a slight decrease in antibacterial properties, compressive strength and toughness, and a decrease in degradation rate. The reason for the reduction in antibacterial properties is that too much protocatechuic acid may cause it to form agglomerates in the material, thereby affecting the uniform distribution with quaternized chitosan, thereby reducing the antibacterial activity. The reason for the decrease in mechanical properties is that a high protocatechuic acid ratio may destroy the uniform structure inside the material, resulting in a weakening of the intermolecular binding force, thereby reducing the compressive strength and toughness. The reason for the reduction in degradation rate is that a high protocatechuic acid ratio may affect the pore structure of the material, slow down the penetration rate of the degradation medium, and thus reduce the degradation efficiency.

[0081] The main difference between Comparative Example 4 and Example 1 is that the mass ratio of protocatechuic acid to quaternized chitosan in Comparative Example 4 is 1:4, while that in Example 1 is 1:2. As can be seen from the table, the low proportion of protocatechuic acid (1:4) leads to a decrease in antibacterial properties, compressive strength, toughness and degradation rate. The reason for the reduction in antibacterial properties is that too low a proportion of protocatechuic acid will lead to a lack of sufficient phenolic hydroxyl groups in the material, weakening the antibacterial activity of quaternized chitosan. The reason for the decrease in mechanical properties is that too low a proportion of protocatechuic acid will reduce the intermolecular hydrogen bonding effect and reduce the structural stability of the material, thereby leading to a decrease in compressive strength and toughness. The reason for the reduction in degradation rate is that insufficient proportion of protocatechuic acid may weaken the hydrolysis performance of the material, thereby affecting the degradation efficiency.

[0082] The main difference between Comparative Example 5 and Example 1 is that the gelatin in Comparative Example 5 has not been grafted with 2,3-epoxypropyltrimethylammonium chloride. As can be seen from the table, the ungrafted gelatin leads to a significant decrease in antibacterial properties, compressive strength, toughness and degradation rate. The reason for the decrease in antibacterial properties is that the grafting treatment can introduce quaternary ammonium salt groups, which enhances the antibacterial activity of gelatin, while the ungrafted gelatin itself has weak antibacterial ability. The reason for the decrease in mechanical properties is that the grafting treatment can improve the rigidity of the molecular chain of gelatin and its compatibility with other components, while the ungrafted gelatin molecular chain is soft and cannot effectively enhance the mechanical properties of the material. The reason for the decrease in degradation rate is that the grafting treatment can adjust the water solubility and pore structure of the material and promote degradation, while the ungrafted gelatin has poor degradation performance.

[0083] The main difference between Comparative Example 6 and Example 1 is that the grafting rate of quaternary ammonium salt grafted gelatin in Comparative Example 6 is 25%, while the grafting rate of Example 1 is higher. It can be seen from the table that the insufficient grafting rate (25%) leads to a decrease in antibacterial properties, compressive strength, toughness and degradation rate. The reason for the reduction in antibacterial properties is that when the grafting rate is low, the amount of quaternary ammonium salt groups introduced is insufficient, which weakens the antibacterial efficacy of gelatin. The reason for the decrease in mechanical properties is that the lower grafting rate may lead to insufficient internal cross-linking of the material, weakening the intermolecular bonding force, thereby reducing compressive strength and toughness. The reason for the decrease in degradation rate is that when the grafting rate is low, the pore structure and solubility optimization effect of the material is insufficient, thereby slowing down the degradation rate of the material.

[0084] The main difference between Comparative Example 7 and Example 1 is that the grafting rate of quaternary ammonium salt grafted gelatin in Comparative Example 7 is 45%, while the grafting rate of Example 1 is moderate. As can be seen from the table, although the antibacterial property is improved when the grafting rate is too high (45%), the compressive strength, toughness and degradation rate are slightly reduced. The reason for the improvement of antibacterial property is that when the grafting rate is high, the amount of quaternary ammonium salt groups introduced increases, which enhances the antibacterial effect. The reason for the decrease in mechanical properties is that the grafting rate is too high, which may cause excessive cross-linking inside the material, reduce the flexibility of the molecular chain, and thus weaken the compressive strength and toughness. The reason for the decrease in degradation rate is that the excessively high grafting rate may cause the pore structure of the material to be partially filled, affecting the penetration of the degradation medium, thereby slowing down the degradation rate.

[0085] By comparing the performance of Example 1 with the comparative examples, it can be seen that the modification of protocatechuic acid, quaternization treatment and optimization of the grafting rate play a key role in the comprehensive performance of the material. The antibacterial properties, mechanical properties and degradation rates of the unmodified or treated comparative examples (such as comparative examples 1 and 2) are significantly lower than those of the embodiments, indicating that the modification treatment can significantly improve the antibacterial properties, compressive strength, toughness and degradation properties of the material. The adjustment of the mass ratio of protocatechuic acid to quaternized chitosan (such as comparative examples 3 and 4) has an important influence on the performance. Too high or too low a ratio will lead to a decrease in antibacterial properties and mechanical properties, indicating that a suitable protocatechuic acid ratio (such as 1:2 in Example 1) can better balance the performance. Comparative example 5, which has not been grafted, shows the worst comprehensive performance, indicating that quaternary ammonium salt grafting treatment is crucial to improving antibacterial properties and mechanical properties. In addition, the optimization of the grafting rate (such as comparative examples 6 and 7) also has a significant impact on the performance. Too low a grafting rate (Comparative Example 6) will lead to insufficient antibacterial properties, mechanical properties and degradation rates, while too high a grafting rate (Comparative Example 7) can improve antibacterial properties, but will lead to a decrease in mechanical properties due to excessive cross-linking, and even affect degradation properties. Therefore, a moderate grafting rate (such as Example 1) is the key to obtaining the best comprehensive performance. Overall, Examples 1 to 4 achieve a comprehensive improvement in antibacterial properties, mechanical properties and degradation properties through a reasonable protocatechuic acid ratio, quaternary ammonium modification and optimization of the grafting rate, showing excellent performance, while the comparative examples show a trend of declining performance when unmodified, under-treated or over-treated. This shows that the optimization of material properties requires comprehensive regulation of multiple parameters, such as coordinated optimization of quaternary ammonium modification, protocatechuic acid ratio and grafting rate, to achieve the best balance of material properties.

[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. An antibacterial and degradable sponge material, characterized in that: The invention comprises the following components in parts by weight: 8-12 parts of protocatechuic acid modified quaternized chitosan, 10-20 parts of quaternary ammonium salt grafted gelatin, 5-10 parts of sodium alginate, 8-15 parts of polyhydroxybutyrate, 8-12 parts of polycaprolactone, 8-12 parts of polylactic acid-glycolic acid copolymer, 3-8 parts of gallic acid, 4-8 parts of foaming agent, 2-5 parts of nanocellulose, 0.5-2.0 parts of vitamin E, 8-16 parts of polyethylene glycol, 1.0-3.0 parts of triethylamine and 10-20 parts of dimethyl sulfoxide; The protocatechuic acid modified quaternary ammonium chitosan is prepared from the following components in parts by weight: 6-12 parts of quaternary ammonium chitosan, 100 parts of 0.5wt.% acetic acid solution, 6-15 parts of protocatechuic acid, 50 parts of anhydrous ethanol, 150-200 parts of 2-(N-morpholine) ethanesulfonate potassium buffer with a pH of 5.5, 6-10 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, and 3.0-5.0 parts of N-hydroxysuccinimide; The quaternized chitosan is obtained by modifying chitosan with 2,3-epoxypropyltrimethylammonium chloride; The quaternary ammonium salt grafted gelatin is obtained by modifying gelatin with 2,3-epoxypropyltrimethylammonium chloride.

2. The antibacterial and degradable sponge material according to claim 1, characterized in that: The preparation method of the protocatechuic acid modified quaternized chitosan is as follows: by weight, 12 to 30 parts of quaternized chitosan are used as raw materials, and the quaternized chitosan is uniformly dissolved in 100 parts of 0.5wt% acetic acid solution to obtain solution A; 6 to 10 parts of protocatechuic acid are used as raw materials, and the quaternized chitosan is dissolved in 50 parts of anhydrous ethanol to obtain a mixed solution; 150 to 200 parts of 2-(N-morpholine) ethanesulfonic acid potassium buffer with a pH of 5.5 and 6 to 10 parts of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added to the mixed solution, and the mixture is stirred for 60 to 90 minutes to obtain solution B; 3.0 to 5.0 parts of N-hydroxysuccinimide are slowly added to the solution B, and the stirring is continued for 120 to 180 minutes to obtain solution C; the solution C is added dropwise to the solution A, and the mixture is stirred at room temperature for 8 to 12 hours until the reaction is completed; after the reaction is completed, the mixed solution is heated to 4000 ℃ and heated to 1000 ℃. The Da dialysis membrane was dialyzed for 48-54 hours, and then the dialysate was centrifuged at 10000-12000 rpm for 20-30 minutes. After centrifugation, the supernatant was placed in a freeze dryer and freeze-dried for 4-8 hours at a vacuum degree of 4-10 Pa and a temperature of -30--10°C to finally obtain protocatechuic acid-modified quaternary ammonium chitosan.

3. An antibacterial and degradable sponge material as claimed in claim 1 or 2, characterized in that: The preparation method of the quaternary ammonium chitosan is as follows: by weight, 14 to 20 parts of chitosan and 8.0 to 15.0 parts of 2,3-epoxypropyltrimethylammonium chloride are used as raw materials, and the mixture is uniformly mixed with 200 parts of deionized water, and then placed in a three-necked flask, and stirred and refluxed for 20 to 28 hours at 75 to 85° C. until the reaction is completed; after the reaction is completed, the obtained solution is passed through a dialysis membrane with a molecular weight cutoff value of 1400, and dialyzed in distilled water for 60 to 72 hours; then the dialyzate is placed in a rotary evaporator, and concentrated to 1 / 5 to 1 / 10 of the original volume at 40 to 50° C. and a vacuum degree of -0.08 to -0.09 MPa; after the concentration is completed, the concentrated solution is placed in a freeze dryer, and freeze-dried for 6 to 12 hours at a vacuum degree of 4 to 10 Pa and a temperature of -30 to -10° C., so as to finally obtain loose powdery quaternary ammonium chitosan.

4. The antibacterial and degradable sponge material according to claim 2, characterized in that: The mass ratio of the protocatechuic acid to the quaternized chitosan is 1:(2.0-3.0).

5. The antibacterial and degradable sponge material according to claim 1, characterized in that: The preparation method of the quaternary ammonium salt grafted gelatin is as follows: by weight, 10 to 20 parts of gelatin are used as raw materials, dissolved in 150 to 200 parts of 10wt.% phosphate buffer, stirred at 50 to 60°C for 30 to 60 minutes until completely dissolved; then, the pH of the solution is adjusted to 8.5 to 9.0 with 1 mol / L sodium hydroxide solution, and the solution is kept in a stirring state; 40 to 50 parts of 50wt.% 2,3-epoxypropyltrimethylammonium chloride solution are slowly added to the solution in a dropwise manner, and the stirring reaction is continued at 50 to 60°C for 12 to 15 hours until the reaction is completed; the reaction solution is poured into a dialysis bag with a molecular weight cutoff value of 3000 to 3500 Da, dialyzed in deionized water for 20 to 40 hours, and the deionized water is replaced every 5 hours; the dialyzed solution is placed in a -20 to 40°C environment and frozen for 10 to 14 hours, and finally the quaternary ammonium salt grafted gelatin is obtained.

6. An antibacterial and degradable sponge material as claimed in claim 1 or 4, characterized in that: The grafting rate of the quaternary ammonium salt grafted gelatin is 30% to 40%.

7. The antibacterial and degradable sponge material according to claim 1, characterized in that: The foaming agent is sodium carbonate or sodium citrate.

8. The antibacterial and degradable sponge material according to claim 1, wherein the average pore size of the antibacterial and degradable sponge material is 50-200 μm and the porosity is 50%-90%.

9. The antibacterial and degradable sponge material according to claim 1, wherein the nanocellulose is Tempo-oxidized nanocellulose, and the surface carboxyl content of the nanocellulose is 1.0-2.0 mmol / g.

10. The method for preparing an antibacterial and degradable sponge material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The present invention also provides a method for preparing an antibacterial and degradable sponge material, comprising the following steps: adding the mixture into a mixer according to a weight ratio, stirring at a rate of 300 to 500 rpm, stirring for 60 to 100 minutes, and controlling the system temperature at 40 to 50°C until a uniform mixed solution is formed; placing the obtained mixed solution in a vacuum environment, controlling the vacuum degree to be -0.08 to -0.1 MPa, and performing a degassing treatment for 10 to 20 minutes; pouring the degassed mixed solution into a mold, performing a foaming treatment in a vacuum environment, controlling the vacuum degree to be -0.06 to -0.08 MPa, and performing heat preservation and foaming at 40 to 50°C for 20 to 24 hours. h, until a uniform semi-cured material is formed; the semi-cured material formed after foaming is placed in an oven, and subjected to a primary drying treatment at 40-55°C, during which the humidity is controlled at 30%-50%, and the drying time is 3-6 h; finally, a final drying treatment is carried out at 50-55°C, the humidity is controlled at 2-6%, and the drying time is 6-10 h, to finally obtain an antibacterial and degradable sponge material.

Citation Information

Patent Citations

  • Sponge

    CN106700581A

  • Degradable water-absorbing sponge

    CN109054102A

  • Preparation method of chitosan-gallic acid copolymer and application

    CN106084088A

  • Preparation method of chitosan-protocatechuic acid graft copolymer film

    CN106220876A

  • Oxidized chitosan quaternary ammonium salt and collagen crosslinking method

    CN106366333A

Cited By

  • PVC (polyvinyl chloride) fireproof plate prepared from oyster shells and preparation method of PVC fireproof plate

    CN120988407A

  • Nanometer type multifunctional negative ion material and preparation method thereof

    CN121488974A

  • Antibacterial lasting skin-friendly sanitary towel and preparation method thereof

    CN122057062A